2010
DOI: 10.1002/j.0022-0337.2010.74.10.tb04972.x
|View full text |Cite
|
Sign up to set email alerts
|

Jordanian Dental Students’ Knowledge and Attitudes in Regard to Child Physical Abuse

Abstract: The aim of this study was to investigate Jordanian dental students' educational experience, attitudes, and knowledge regarding child physical abuse. Data were collected from a self-administered questionnaire completed by 441 undergraduate and postgraduate dental students in both dental schools in Jordan. Descriptive statistics were used to report responses to each question. The chi-square test was used to analyze the relationship between students' responses and level of education; the difference was considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 11 publications
9
10
0
Order By: Relevance
“…However, the results in this study showed that healthcare professionals had poor knowledge on how to identify potential child maltreatment cases. This has been reported in similar studies in other parts of the world (Al‐Jundi et al, ; Cairns, Mok, & Welbury, ; Sonbol et al, ; Thomas, Straffon, & Inglehart, ). For example, Kirankumar et al () found that medical professionals of North Karnataka's Bagalkot District in India had poor knowledge as they undervalued the impact of child abuse.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, the results in this study showed that healthcare professionals had poor knowledge on how to identify potential child maltreatment cases. This has been reported in similar studies in other parts of the world (Al‐Jundi et al, ; Cairns, Mok, & Welbury, ; Sonbol et al, ; Thomas, Straffon, & Inglehart, ). For example, Kirankumar et al () found that medical professionals of North Karnataka's Bagalkot District in India had poor knowledge as they undervalued the impact of child abuse.…”
Section: Discussionsupporting
confidence: 83%
“…In countries with relatively good child dental care system, dentists tended to be the first professionals to discover physical abuse cases, as the most common indicators are located within the mouth and surrounding regions (Laud, Gizani, Maragkou, Welbury, & Papagiannoulis, ). In addition, on the basis of how regularly dental practitioners are in contact with children and their families, they are in a favourable position to observe abnormal child–parent behaviour and to identify and report suspected cases of child maltreatment (Al‐Jundi, Zawaideh, & Al‐Rawi, ).…”
Section: Introductionmentioning
confidence: 99%
“…Jordan et al also found less than half of the students responded correctly to the questions regarding their knowledge of signs of child abuse . In studies from other countries, it was revealed that dental students had insufficient knowledge about child abuse and they did not feel ready for their role of protecting children .…”
Section: Discussionsupporting
confidence: 54%
“…The average time required to answer the questions was 10 min. The questionnaire was composed of 29 questions, and it was based on similar previous studies .…”
Section: Methodsmentioning
confidence: 99%
“…The need for greater education in this field has been expressed even among health professionals with immense levels of engagement with child protection [ 32 ]. In Jordan, 124 (32.4%) undergraduates and 23 (39.7%) postgraduates dental students did not know where to report child abuse and neglect [ 33 ]. Strong endorsement advocating the need for education regarding all applied ethics topics is not surprising as lack of relevant training has been noted in other countries such as Germany [ 34 ] and the USA [ 35 ].…”
Section: Discussionmentioning
confidence: 99%